Nigerian Literary Imagination and the Nationhood Project - Falola, Toyin. author. (orcid)0000-0001-9512-1021 Link aut Link
XXI, 286 p. 21 illus.
Keywords: This view of Nigerian Literature puts the ideological contentions and contradictions of old in perspective. Toyin Falola, in this effusion, not only charts the course for the reinvention and invention of the Nigerian Nation through its literature but troubles the literary taboos as well as the theoretical postures and leanings in the art of Nigerian literary artists. -Adedoyin Aguoru, President, African Association for Japanese Studies This fascinating and original piece of scholarship by Nigeria’s most celebrated historian has successfully linked the wide and varied Nigerian literature to the complexities of the nation. The indomitable Toyin Falola maps cogently the cultural, elitist, ideological, feminized and the fetishized aspects of the Nigerian experience. The book masterfully shows us a space that is complicated, inhabited by enigmatic people who see their country as peculiar and unique. - Bosede Funke Afolayan, University of Lagos, Nigeria, and editor of Nigerian Female Dramatists: Expression, Resistance, Agency This book explores how modern Nigerian fiction is rooted in writers’ understanding of their identity and perception of Nigeria as a country and home. Surveying a broad range of authors and texts, the book shows how these fictionalized representations of Nigeria reveal authentic perceptions of Nigeria’s history and culture today. Many of the lessons in these works of literature provide cautionary tales and critiques of Nigeria, as well as an examination of the lasting impact of colonialism. Furthermore, the book presents the nation as both the framework and subject of its narrative. By conducting literary analyses of Nigerian fiction with historical reference points, this work demonstrates how Nigerian literature can convey profound themes and knowledge that resonates with audiences, teaching Nigerians and non-Nigerians about the colonial and postcolonial experience.The chapters cover topics on nationhood, women’s writing, postcolonial modernity, and Nigerian literature in the digital age. Toyin Falola is the Jacob and Frances Sanger Mossiker Chair in the Humanities and a Distinguished Teaching Professor at the University of Texas at Austin, USA. He is a recipient of many distinguished awards, including 16 honorary doctorates.